Semileptonic and Missing Energy B Decays at Belle II - Giovanni Gaudino (Particles)
The Belle II experiment has collected a 364 fb−1 sample of collisions at the <semantics>Υ(4S)</semantics> resonance. This dataset, with its low particle multiplicity and well-constrained initial state, provides an ideal environment for studying semileptonic and missing energy B decays. In this paper, I will present recent results on these decays, emphasizing their impact on the determination of CKM matrix elements and potential new physics. I will also discuss the techniques used for missing energy reconstruction and the challenges of signal-background discrimination. Future analysis prospects with larger datasets will also be highlighted.